Ramadan Recitation Activities 1445 H in Increasing Employee Religion at the Ministry of Religion of Nganjuk Regency - Mukhammad Alfani; Puteri Rahmah Safira; Fathurrozak; Rosita Andika Sahazfana; Shinta Kristantiara Samudra; Mufidatun Nur Aini; Mohammad Fahmi Shahab (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
This article discusses the implementation of Ramadan recitation activities at the Nganjuk Regency Ministry of Religious Affairs in increasing spiritual awareness and employee religiosity. In this context, the hadith that emphasizes the importance of worshipping Allah as if we see Him serves as the foundation for the recitation activity. Despite the importance of these activities, there are challenges in increasing employees' interest in attending them, such as boredom, time constraints, digital distractions, and lack of purpose or vision. The research was conducted using a qualitative method through interviews, observations, and documentation to evaluate the implementation of Ramadan recitation activities. The results showed that Ramadan recitation is an important tool to increase faith, piety, and religious understanding. The recitation program is carried out simply by involving religious expert speakers and the goal is to get closer to Allah SWT and increase worship. The author provides solutions to increase employee interest in participating in Ramadan recitation, including creating a pleasant atmosphere, adjusting activity schedules, involving members in planning, and conveying the importance of maintaining worship. Thus, the Ramadan recitation activity at the Nganjuk Regency Ministry of Religious Affairs is not only a place to increase spiritual awareness, but also a means to get closer to God and increase worship.